Soil Alveolata diversity in the undisturbed steppe and wheat agrocenoses under different tillage - N. B. Naumova; P. A. Barsukov; O. A. Baturina; O. A. Rusalimova; M. R. Kabilov (Вавиловский журнал генетики и селекции)
Microeukaryotes are vital for maintaining soil quality and ecosystem functioning, however, their communities are less studied than bacterial and fungal ones, especially by high throughput sequencing techniques. Alveolates are important members of soil microbial communities, being consumers and/or prey for other microorganisms. We studied alveolate diversity in soil under the undisturbed steppe (US) and cropped for wheat using two tillage practices (conventional, CT, and no-till, NT) by amplifying the ITS2 marker with ITS3_KYO2/ITS4 primers and sequencing amplicons using Illumina MiSeq. A total of 198 Alveolata OTUs were identified, with 158 OTUs attributed to the Ciliophora phylum, containing five classes: Litostomatea, Spirotrichea and Oligohymenophorea, Nassophorea and Phyllopharyngea. Litostomatea and Phyllopharyngea were more abundant in US as compared with CT and NT. The observed OTU richness was higher in US than in CT and NT. The β-biodiversity of soil ciliates also very distinctly differentiated the US field from CT and NT. In the US, Nassophorea and Spirotrichea correlated positively with sand and negatively with clay, silt and SOM contents. This is the first report about soil ciliates diversity in Siberia as assessed by metabarcoding technique. The revealed clear effect of land use on the relative abundance of some taxa and a lack of tillage effect suggest the importance of the quantity and quality of plant material input for shaping the prey for ciliates. The ITS-metabarcoding technique was used for the first time in the research of ciliates diversity; further studies, embracing diverse aspects of soil ciliates by combining -omics methodology with the traditional one, are needed to get a better insight on the ecological roles of the main ciliate taxa in the complex soil system.